Immediate outcome of acute glomerulonephritis in children - experience in a tertiary level hospital (Bangladesh Journal of Medical Science, 2012)
Acute Glomerulonephritis (AGN) in children is common in our country and possesses a significant hospital load. AGN is principally a disease of children were poverty, overcrowding and poor hygiene are prevailing. It is a significant cause of morbidity and mortality in developing countries. Objective : To see the immediate outcome of the children with AGN. Materials and Mithods: Sixty two cases of AGN were enrolled in this study. All cases were collected from paediatric department of Sir Salimullah Medical College (SSMC) and Mitford Hospital, Dhaka during the period of September 2000 to November 2001. A thorough history were taken and chemical examination were carried out and the patient were observed during hospitalization and after discharge and recorded in a preformed questionnaire. Results: Total number of cases were sixty two. Eighty one percent were between 6 years to 12 years of age with male predominance. Most of then came from poor socioecononic status (81%). All patients had generalized edema. Eighty one percent had reduced micturation, 29% had gross haematuria, 13% ascitis, 3% anuria, 2% had epistaxis with convulsion and coma. Eighty four percent had hypertension, 50% had infected scabies. Urinary RBC was found in 93.55% cases and RBC cast in 70-96% cases, blood urea over 40 mg/dl in 30.64% patient and serum creatinine over 1.0 mg/dl in 9.88% patients. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9499 BJMS 2011; 10 (4): 269-274